Предмет: Математика, автор: fidrik2015

1) ((m-(2*sqrt(mn))+n)/(m-n))
2) ((a+3*sqrt(a))/(a-9)
3) a/(a-1)-(sqrt(a))/(sqrt(a)+1)

Ответы

Автор ответа: snow99
1
1)
 \frac{m - 2 \sqrt{mn} + n }{m - n}  =  \frac{ {( \sqrt{m}  -  \sqrt{n} )}^{2} }{( \sqrt{m}  - \sqrt{n} )( \sqrt{m}  +  \sqrt{n}) }  =  \frac{ \sqrt{m}  -  \sqrt{n} }{ \sqrt{m} +  \sqrt{n}  }
2)
 \frac{a + 3 \sqrt{a} }{a - 9}  =  \frac{ \sqrt{a}( \sqrt{a}  + 3)}{( \sqrt{a}  - 3)( \sqrt{a}  + 3)}  =  \frac{ \sqrt{a} }{ \sqrt{a}  - 3}
3)
 \frac{a}{a - 1}  -  \frac{ \sqrt{a} }{ \sqrt{a} + 1 }  =  \frac{a}{( \sqrt{a}  - 1)( \sqrt{a} + 1) }  -  \frac{ \sqrt{a}( \sqrt{a} - 1)  }{( \sqrt{a} + 1)( \sqrt{a}  - 1) }  =  \frac{a - a +  \sqrt{a} }{a - 1}  =  \frac{ \sqrt{a} }{a - 1}
Похожие вопросы
Предмет: Литература, автор: apastuhova91
Предмет: Математика, автор: grodionova1414
Предмет: Математика, автор: Аноним